1995
DOI: 10.1111/j.0022-3646.1995.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYLOGENETIC POSITION OF BOTRYOCOCCUS BRAUNII (CHLOROPHYCEAE) BASED ON SMALL SUBUNIT RIBOSOMAL RNA SEQUENCE DATA1

Abstract: A small subunit ribosomal RNA (16S‐like rRNA) in the hydrocarbon‐rich microalga Botryococcus braunii Kützing (Chlorophyceae) was amplified using RNA polymerase chain reaction, and its sequence was determined. The sequence data of B. braunii were analyzed with those of several other algae in order to determine phylogenetic relationships among these algae. Phylogenetic analysis indicated B. braunii to be a member of the Chlorophyta and possibly related to Characium vacuolatum and Dunaliella parva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 15 publications
1
29
1
Order By: Relevance
“…Analyses of small subunit ribosomal RNA (rRNA) sequence data have facilitated clarification of phylogenetic relationships among microalgae 15), 16) . The phylogenetic position of B. braunii has been determined using 16S-like rRNA sequence data 17) . The 16S-like rRNA in the hydrocarbon-rich microalga B. braunii was amplified using RNA polymerase chain reaction, and its sequence was determined.…”
Section: Phylogenetic Position Of B Braunii Based Onmentioning
confidence: 99%
“…Analyses of small subunit ribosomal RNA (rRNA) sequence data have facilitated clarification of phylogenetic relationships among microalgae 15), 16) . The phylogenetic position of B. braunii has been determined using 16S-like rRNA sequence data 17) . The 16S-like rRNA in the hydrocarbon-rich microalga B. braunii was amplified using RNA polymerase chain reaction, and its sequence was determined.…”
Section: Phylogenetic Position Of B Braunii Based Onmentioning
confidence: 99%
“…is one of microalgae type included in the Chlorophyceae class with the highest lipid content compared to other types of microalgae, which amounted to 75% of the dry biomass weight (Sawayama et al, 1995;Chisti, 2007). Botryococcus has a main fatty acid profile such as oleic acid (C18: 1, 54.9%), palmitic acid (C16: 0, 12.2%), linolenic acid (C18: 3, 5.5%), stearic acid ( C18: 0, 3.9%) and linoleic acid (C18: 2, 5.5%), these fatty acids can be used for biodiesel feedstock ( Knothe, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis based on morphological and/or molecular data contributed to the idea that a set of coccalorganized chlorophytes also belong to the Chlamydophyceae, i.e., Characium vacuolatum , and Botryococcus braunii (Sawayama et al 1995). Lewis et al (1992) compared morphological and molecular data and showed that chlorococcalean species that were characterized by a clockwise orientation of the basal bodies were also phylogenetically closely related to the Chlamydophyceae.…”
Section: Introductionmentioning
confidence: 99%